In vitro Antagonistic Mechanisms of Trichoderma spp. and Talaromyces flavus to Control Gaeumannomyces graminis var. tritici the Causal Agent of Wheat Take-all Disease - Seddighe Mohammadi; Leila Ghanbari (Turkish Journal of Agriculture: Food Science and Technology)
Wheat take-all disease caused by Gaeumannomyces graminis var. tritici has recently been detected in different regions of Iran. With respect to biocontrol effect of Trichoderma spp. on many pathogenic fungi, seven isolates of Trichoderma and four isolates of Talaromyces were in vitro evaluated in terms of their biological control against the disease causal agent. In dual culture test the five isolates showed efficient competition for colonization against pathogenic fungus and the highest percentages of inhibition belonging to Talaromyces flavus 60 and Talaromyces flavus 136 were 59.52 and 57.61%, respectively. Microscopic investigations showed that in regions where antagonistic isolates and Gaeumannomyces graminis var. tritici coincide, hyphal contact, penetration and fragmentation of Gaeumannomyces graminis var. tritici were observed. Investigating the effect of volatile and non-volatile compounds at 10 ml concentration showed that the highest inhibition percentage on mycelium growth of the pathogen caused by T. harzianum (44.76%) and T. longibrachiatum (52.38%) respectively.